Electrodeposited PEDOT:Nafion Composite for Neural Recording and Stimulation. Issue 19 (5th September 2019) - Carli, Stefano; Bianchi, Michele; Zucchini, Elena; Di Lauro, Michele; Prato, Mirko; Murgia, Mauro; Fadiga, Luciano; Biscarini, Fabio
Abstract: Microelectrode arrays are used for recording and stimulation in neurosciences both in vitro and in vivo. The electrodeposition of conductive polymers, such as poly(3, 4‐ethylene dioxythiophene) (PEDOT), is widely adopted to improve both the in vivo recording and the charge injection limit of metallic microelectrodes. The workhorse of conductive polymers in the neurosciences is PEDOT:PSS, where PSS represents polystyrene‐sulfonate. In this paper, the counterion is the fluorinated polymer Nafion, so the composite PEDOT:Nafion is deposited onto a flexible neural microelectrode array. PEDOT:Nafion coated electrodes exhibit comparable in vivo recording capability to the reference PEDOT:PSS, providing a large signal‐to‐noise ratio in a murine animal model. Importantly, PEDOT:Nafion exhibits a minimized polarization during electrical stimulation, thereby resulting in an improved charge injection limit equal to 4.4 mC cm −2, almost 80% larger than the 2.5 mC cm −2 that is observed for PEDOT:PSS. Abstract : Poly(3, 4‐ethylene dioxythiophene)(PEDOT):Nafion coatings electrodeposit on a neural microelectrode array provided an improved charge injection limit when subjected to sub‐millisecond current pulses and comparable recording capability to the PEDOT:polystyrene‐sulfonate control. The results outline how PEDOT:Nafion is particularly beneficial for biomedical applications that require current flow while minimizing related tissue damage.